Kolaboratif: Kerangka Kerja Konselor Masa Depan - Afdal Afdal (Jurnal Konseling dan Pendidikan, 2015)
The successful implementation of guidance and counseling in schools is not only the duty of counselor alone, but further a common task among school personnel (both the principal, teachers, class guardian, administration officials  and other students) and the school environment (parents , communities, and others). This paper presents ideas with regard to the importance of establishing collaborative with other persons to help optimal students development.